Schumpeter and the endogeneity of technology : some American perspectives - Rosenberg, Nathan, 1927-2015 (Graz Schumpeter lectures, 2000)
"This book explores Schumpeter's views as an economist who was, long ago, committed to the notion of the endogeneity of technology. His mature writings offer illuminating historical analyses of how and why some social systems have managed to generate innovation. This element of his vision deserves far more attention than it has so far received, and this book redresses the balance. Moreover, bringing us up-to-date, Nathan Rosenberg explores the ways in which the concept of endogeneity illuminates recent American economic history."--Jacket